2021
DOI: 10.1039/d0nr07962f
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser driven precessing magnetic gratings

Abstract: Manipulation and detection of spins at the nanoscale is of considerable contemporary interest as it may not only facilitate a description of fundamental physical processes but also plays a critical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The in situ experiments were performed in the Göttingen UTEM 70 , which is based on a thermal field-emission TEM (JEM 2100F, JEOL Ltd). Achieving temporal resolutions in the femtosecond regime 70 72 , UTEM has enabled stroboscopic real-space movies of numerous processes, including strain wave dynamics 34 , 73 , 74 , ultrafast demagnetization 75 77 and the evolution of structural phase transformations 33 , 35 . In the current experiments, the electron gun is operated in the extended Schottky regime, yielding a continuous electron beam with an initial energy spread of 0.5 eV at variable electron energies from 80 to 200 keV and typical beam currents of 10–50 pA in the sample region.…”
Section: Methodsmentioning
confidence: 99%
“…The in situ experiments were performed in the Göttingen UTEM 70 , which is based on a thermal field-emission TEM (JEM 2100F, JEOL Ltd). Achieving temporal resolutions in the femtosecond regime 70 72 , UTEM has enabled stroboscopic real-space movies of numerous processes, including strain wave dynamics 34 , 73 , 74 , ultrafast demagnetization 75 77 and the evolution of structural phase transformations 33 , 35 . In the current experiments, the electron gun is operated in the extended Schottky regime, yielding a continuous electron beam with an initial energy spread of 0.5 eV at variable electron energies from 80 to 200 keV and typical beam currents of 10–50 pA in the sample region.…”
Section: Methodsmentioning
confidence: 99%
“…Rubiano da Silva et al recently mapped the partial demagnetization of vortices in nanoscale disks of permalloy with 100 nm spatial resolution and 700 fs temporal resolution, 125 shown in Figure 5a-c. Cao et al reported on demagnetization of permalloy with a grating pattern caused by interference in the exciting laser, resulting in a coherently precessing magnetic grating, 126 shown in Figure 5d. Zhang et al observed a peculiar sequence of subpicosecond demagnetization, recovery over 3 ps, and decay to a paramagnetic state over 12 ps of the spiral spin texture in Mn-Ni-Ga. 100 Despite this methodical progress, ultrafast Lorentz microscopy still needs to overcome a number of experimental challenges.…”
Section: Ultrafast Lorentz Transmission Electron Microscopymentioning
confidence: 99%
“…Ultrafast Lorentz microscopy has been employed to study several types of dynamics, including domain wall motion under an oscillating magnetic field 109 or laserinduced thermal gradients, 110,124 laser-induced demagnetization, 100,[124][125][126] and current-driven vortex oscillations. 127 In two recent examples, Möller et al investigated the response of a magnetic vortex to an applied highfrequency current.…”
Section: Ultrafast Lorentz Transmission Electron Microscopymentioning
confidence: 99%
“…Beyond stationary imaging, the advent of in-situ and time-resolved electron microscopy allow for the observation of transient phenomena and non-equilibrium dynamics [34]. Achieving temporal resolutions in the femtosecond regime [35][36][37][38][39], ultrafast transmission electron microscopy (UTEM) has enabled stroboscopic real-space movies of numerous processes, including strain wave dynamics [40][41][42], ultrafast demagnetization [43][44][45], and the evolution of structural phase transformations [46,47]. Moreover, in the form of photon-induced near-field electron microscopy (PINEM), UTEM permits quantitative, high-resolution imaging of nano-optical fields [12-14, 48, 49].…”
Section: Introductionmentioning
confidence: 99%